Pengukuran Kualitas Pelayanan Rumah Sakit di Aceh dengan Model HSQ-Metrix - Iwan Budhiarta; Muttaqin Samuthi (Jurnal Maksipreneur, 2019)
From the preliminary study, the results stated that there was a tendency for an increase in healthcare tourism of Acehnese visits to Malaysia from year to year. The chaotic condition represent of the quality of health services in Indonesia, especially in Aceh, that must be sought for the best solution. Therefore research was carried out with the title "Analysis of Hospital Services Quality in Aceh with the HSQ-Metrix model" which was more comprehensive in assessing the quality of hospital healthcare services. This model is a latest development of HospitalQual compiled by Itumalla et al. in 2014. This model includes the variable Religious Obedience or Religion as one of the quality requirements for healthcare services in hospitals that are in accordance with Sharia principles. Finally, the quality of service at RSUD Dr. Zainoel Abidin still needed a further improvement. HSQ-Metrix values between patient expectations and patient perceptions are still in negative results. This value described that RSUD dr. Zainoel Abidin has not provided services in accordance with patient expectations yet. Perception from the high-level management of RSUD dr. Zainoel Abidin regarding the services desired by non-BPJS patients was not in accordance with the wishes of actual patients. The practices of the quality standards set by the RSUD dr. Zainoel Abidin has not been fully implemented. The recommend will be to to follow up on the concept of proposals in improving the quality of inpatient services, especially on things that have not met consumer expectations. The results of this study are expected to be a supporting material and a driver towards improving the quality of healthcare services in hospitals throughout the Aceh region.